Experimental investigation on continuous reinforced SCC deep beams and Comparisons with Code provisions and models. (15th January 2017) - Khatab, M.A.T.; Ashour, A.F.; Sheehan, T.; Lam, D.
Highlights: Test results of eight continuous reinforced SCC deep beams and code comparisons are presented. All beams tested failed due to a major diagonal crack formed between load and interior support plates. The shear strength of the beams tested is mainly controlled by concrete compressive strength. For the shear span-to-depth ratio considered, vertical web reinforcement had more influence on shear capacity. The strut-and-tie model recommended by different design codes showed conservative results. Abstract: The test results on eight two-span deep beams made of self-compacting concrete (SCC) are presented and discussed in this paper. The main parameters investigated were the shear span-to-depth ratio, and the amount and configuration of steel reinforcement. All beams failed due to a major diagonal crack formed between the applied mid-span load and the intermediate support separating the beam into two blocks: the first one rotated around the end support leaving the other block resting on the other two supports. Both concrete compressive strength and web reinforcement had a major effect in controlling the shear capacity of the beams tested. For the shear span-to-depth ratio considered, the vertical web reinforcement had more influence on the shear capacity of the specimens than the horizontal web reinforcement. The shear provisions of the ACI 318M-11 are unconservative for most of the beams tested. Comparisons of test results with the strut-and-tie model (STM) suggested by ACI 318M-11, EC2 and CSA23.4-04 showed that the predictions are reasonable for continuous deep beams made with low and medium compressive strength. Although the equation suggested by ACI 318M-11 is very simple, its prediction is more accurate than the STM suggested by different design codes.